Clinical Manifest X-Linked Recessive Adrenoleukodystrophy in a Female - Gyda Hlin Skuladottir Jack; Karolina Malm-Willadsen; Anja Frederiksen; Dorte Glintborg; Marianne Andersen (Case Reports in Neurological Medicine)
Adrenoleukodystrophy (ALD) is a rare X-linked inherited leukodystrophy with a reduced capacity for degradation of very long chain fatty acids (VLCFAs). The intracellular accumulation of VLCFA leads to demyelination in the central nervous system (CNS) and cell destruction in the adrenal glands. ALD primarily affects males; however, females may develop milder symptoms that may be difficult to recognize. The present report describes a 35-year-old female who experienced a feeling of heaviness in the upper and lower limbs, pain in both knees, and difficulty climbing stairs, running, and jumping. Clinical examination revealed decreased sensitivity in the feet, particularly to touch. Deep tendon reflexes in the lower limbs were brisk, and Babinski's sign was present bilaterally. Multiple sclerosis (MS) was excluded, and all clinical and biochemical tests were normal. After two years of progressing symptoms, the patient was reevaluated and plasma levels of VLCFA were found to be elevated. Seven years prior to this finding, the patient had been found to be heterozygous for the missense mutation c.1679C> T, p.Pro560Leu on the ABCD1 gene (ATP-Binding Cassette subfamily D1). In conclusion, the patient's symptoms could be attributed to ALD. The present case underlines the importance of reevaluating family history in women presenting with vague neurological symptoms.